Climate change and tourism – Are we forgetting lessons from the past?. (September 2017) - Weir, Brian
Abstract: There has been increasing interest over the last decade in the issues around climate change and tourism. However, in much of this literature, present climate change is often presented as a new phenomenon, one creating new issues and challenges for researchers and for the tourism industry. But this conceptual paper reminds us that climate change has been a constant through the pre history and history of humanity, and as far as is known, of tourism as well. The paper briefly surveys the history of tourism, linking developments to changes in climate and considering the interactions between the two. Several themes are identified and a number of conclusions presented. The first conclusion is that there may be a confusion about climate change being a 'new' issue, perhaps due to a mistaken perception that climate change = anthropogenic (or human induced) climate change. Secondly, and related to this, is a perceived lack of understanding that climate and climate change has had significant impacts on travel and tourism throughout history. Thirdly, that perhaps current research and teaching in the climate change/tourism arena could benefit from lessons learned from examining past experience in tourism adaptation to climate change.